12-3b=5b-2

Simple and best practice solution for 12-3b=5b-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-3b=5b-2 equation:


Simplifying
12 + -3b = 5b + -2

Reorder the terms:
12 + -3b = -2 + 5b

Solving
12 + -3b = -2 + 5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-5b' to each side of the equation.
12 + -3b + -5b = -2 + 5b + -5b

Combine like terms: -3b + -5b = -8b
12 + -8b = -2 + 5b + -5b

Combine like terms: 5b + -5b = 0
12 + -8b = -2 + 0
12 + -8b = -2

Add '-12' to each side of the equation.
12 + -12 + -8b = -2 + -12

Combine like terms: 12 + -12 = 0
0 + -8b = -2 + -12
-8b = -2 + -12

Combine like terms: -2 + -12 = -14
-8b = -14

Divide each side by '-8'.
b = 1.75

Simplifying
b = 1.75

See similar equations:

| 2y=3x+9 | | 7(3x+9)=-(x-3) | | 9x^4=34x^2-25 | | n-4= | | 3(x-24)=9-2(x-2) | | (21)x*x-6=15x | | 14+3x-4=4x+4 | | 2x^6y^6-2x^7y^5+4x^5y^6+4x^6y^5= | | 4x^2=140 | | x-22=44 | | 3x+2=6x-23 | | 10q(16x+11)= | | 9x^3-6x^2+3= | | (6)x*x-14x=12 | | 2x(3x^3-4x^2+x-8)=0 | | x^2-13x-114= | | 4x^9+8x^8+12x^7+8x^6= | | (8r+3t)-[2-(t+3r)]=0 | | 3(7x+5)=2(4x+3) | | 2x-20=7x | | 9x+6-7x-5=5 | | x-0.19(x)=18 | | -11+3x=20 | | ln(x-2)ln(x)=0 | | (12)a*a-13a=35 | | 2r^3t^3-4r^4t^2= | | 6x+8y^3+300=0 | | 3x+4x+2x=9 | | 3x-6=-3(x+2) | | h(x)=3x^2+6 | | (4x-5)(-x-7)=0 | | -2(-c-12)=-2-12 |

Equations solver categories